Effect of surface functional groups on hydrogen adsorption properties of Pd dispersed reduced graphene oxide. (23rd March 2017) - Das, Tapas K.; Banerjee, Seemita; Pandey, M.; Vishwanadh, B.; Kshirsagar, R.J.; Sudarsan, V.
Abstract: Pd/reduced graphene oxide (Pd-RGO) composites were successfully prepared from graphite and PdCl2 precursors using wet impregnation and reverse micro emulsion methods. From hydrogen adsorption studies it is confirmed that spillover of hydrogen from Pd to graphene layers occurs at room temperature. However, at low temperatures there is negligible spillover effect and this is explained based on lower kinetic energy available with hydrogen atoms to overcome the activation barrier involved in diffusion. Detailed 13 C MAS NMR and Raman spectroscopic studies confirmed that small amounts of structural units (functional groups) like carboxylate and polyacetylenic linkages are retained in Pd-RGO samples prepared by wet impregnation and reverse micro-emulsion methods, respectively. Such structural moieties facilitate the atomic scale mixing of Pd with the graphene layers thereby improving the spillover efficiency. Highlights: Spillover of hydrogen from Pd to graphene layers occurs at room temperature. Carboxylate and polyacetylenic linkages are retained in Pd-RGO samples. Organic structural units facilitate spillover of hydrogen from Pd to graphene.